Microstructure behaviour and influence on thermally grown oxide formation of double‐ceramic‐layer EB‐PVD thermal barrier coatings annealed at 1, 300 °C under ambient isothermal conditions. Issue 10 (6th August 2014) - Bobzin, K.; Bagcivan, N.; Brögelmann, T.; Yildirim, B.
<x xml:space="preserve">Abstract</x> To resist high thermal loads in turbines effectively, turbine blades are protected by thermal barrier coatings in combination with additional air cooling. State‐of‐the‐art yttria stabilised zirconia top coats do not operate at temperatures higher than 1, 200 °C. Promising candidates for alternative top coats are pyrochlores, lanthanum zirconate and gadolinium zirconate. But lifetime of pyrochlores is short because of spallation. However, combinations of yttria stabilised zirconia and lanthanum zirconate or gadolinium zirconate as multilayer systems are promising top layers operating at higher temperatures than yttria stabilised zirconia. Such thermal barrier coatings top coats as double‐ceramic‐layer systems consisting of 7 wt.% yttria stabilised zirconia and lanthanum zirconate or gadolinium zirconate were deposited by Electron Beam‐Physical Vapour Deposition. The focus of the work was set on the influence of the coating design and the microstructure variation generated at different rotating speeds on the adhesion and thermally grown oxide behaviour after isothermal oxidation at 1, 300 °C. Phase formation of the thermal barrier coatings top coats was obtained using X‐ray diffraction. After isothermal oxidation tests for 50 h at 1, 300 °C, both, microstructure change and the formation of the thermally grown oxide were investigated. While the pyrochlore single‐ceramic‐layer are completely spalled off, microstructure of the double‐ceramic‐layer reveals only crack initiation. The thermally grown oxide thickness was determined by means of scanning electron microscopy. A high aluminum and oxygen content in the thermally grown oxide is found using X‐ray spectroscopy. Existence of α‐phase in Al2O3 was proved by X‐ray diffraction. After isothermal testing, no phase transformation can be detected regarding the double‐ceramic‐layer coatings.